It is Necessary to Write About Increasing the Attractiveness of National Tourism Products (In the Case of Artisans) (Texas Journal of Philology, Culture and History, 2022)
This article substantiates the need for the development of regional marketing in Uzbekistan as an initial tool for managing the tourism potential of the regions. Clarifications of the concept and composition of regional marketing, given the requirements for managing the economy of the region, are given, and the role of marketing thinking in shaping the image of the region is shown.